Names, Travelers, Transindividuality: Italo Calvino in the 1970s (ENTHYMEMA, 2012)
Situating the novel within the cultural, literary and political milieu of the period, this article provides a reading of Italo Calvino‟s 1979 hypernovel If on a Winter’s Night a Traveler and its relation to the French literary group Oulipo. It analyzes the work‟s link to questions of authorship and collectivity at the core of 1970s literary, philosophical, and political discourse both in Italy and France. In particular, the analysis concentrates on the function of names in the novel as signifiers of individuality and/or collectivity
Keywords: Italo Calvino; Oulipo; authorship; collectivity; hyper-novel